SUNNY-CP and the MiniZinc challenge*. Issue 1 (10th August 2017) - AMADINI, ROBERTO; GABBRIELLI, MAURIZIO; MAURO, JACOPO
Abstract: In Constraint Programming, a portfolio solver combines a variety of different constraint solvers for solving a given problem. This fairly recent approach enables to significantly boost the performance of single solvers, especially when multicore architectures are exploited. In this work, we give a brief overview of the portfolio solversunny-cp, and we discuss its performance in the MiniZinc Challenge—the annual international competition for Constraint Programming solvers—where it won two gold medals in 2015 and 2016.